Naturally occurring variations in the nod-independent model legume Aeschynomene evenia and relatives: a resource for nodulation genetics - Clémence Chaintreuil (BMC Plant Biology, 2018)
Abstract Background Among semi-aquatic species of the legume genus Aeschynomene, some have the unique property of being root and stem-nodulated by photosynthetic Bradyrhizobium lacking the nodABC genes necessary for the production of Nod factors. These species provide an excellent biological system with which to explore the evolution of nodulation in legumes. Among them, Aeschynomene evenia has emerged as a model legume to undertake the genetic dissection of the so-called Nod-independent symbiosis. In addition to the genetic analysis of nodulation on a reference line, natural variation in a germplasm collection could also be surveyed to uncover genetic determinants of nodulation. To this aim, we investigated the patterns of genetic diversity in a collection of 226 Nod-independent Aeschynomene accessions. Results A combination of phylogenetic analyses, comprising ITS and low-copy nuclear genes, along with cytogenetic experiments and artificial hybridizations revealed the richness of the Nod-independent Aeschynomene group with the identification of 13 diploid and 6 polyploid well-differentiated taxa. A set of 54 SSRs was used to further delineate taxon boundaries and to identify different genotypes. Patterns of microsatellite diversity also illuminated the genetic basis of the Aeschynomene taxa that were all found to be predominantly autogamous and with a predicted simple disomic inheritance, two attributes favorable for genetics. In addition, taxa displaying a pronounced genetic diversity, notably A. evenia, A. indica and A. sensitiva, were characterized by a clear geographically-based genetic structure and variations in root and stem nodulation. Conclusion A well-characterized germplasm collection now exists as a major genetic resource to thoroughly explore the natural variation of nodulation in response to different bradyrhizobial strains. Symbiotic polymorphisms are expected to be found notably in the induction of nodulation, in nitrogen fixation and also in stem nodulation. Subsequent genetic analysis and locus mapping will pave the way for the identification of the underlying genes through forward or reverse genetics. Such discoveries will significantly contribute to our understanding of the molecular mechanisms underpinning how some Aeschynomene species can be efficiently nodulated in a Nod-independent fashion.